2020
DOI: 10.3390/cells9112348
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Isoforms of Neurofibromin Are Required for Proper Spindle Organization and Chromosome Segregation

Abstract: Mitotic spindles are highly organized, microtubule (MT)-based, transient structures that serve the fundamental function of unerring chromosome segregation during cell division and thus of genomic stability during tissue morphogenesis and homeostasis. Hence, a multitude of MT-associated proteins (MAPs) regulates the dynamic assembly of MTs in preparation for mitosis. Some tumor suppressors, normally functioning to prevent tumor development, have now emerged as significant MAPs. Among those, neurofibromin, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(32 citation statements)
references
References 108 publications
3
29
0
Order By: Relevance
“…In an earlier study with primary neurons, we found that neurofibromin, in addition to its colocalization with cytosolic MTs, localizes also in the nucleus and identified a bipartite NLS in the CTD (Figure 1B) as the probable mediator of nuclear entry [37]. Previously thought as an artifact in the skin epithelium, nuclear neurofibromin is detected with a variety of techniques, i.e., immunocytochemistry (e.g., white arrows in Figure 3), subcellular fractionations, or proteomics [28,29,[37][38][39][51][52][53] in all cells of an ectodermal origin.…”
Section: Neurofibromins As Maps and Their Role In Mitosismentioning
confidence: 72%
See 4 more Smart Citations
“…In an earlier study with primary neurons, we found that neurofibromin, in addition to its colocalization with cytosolic MTs, localizes also in the nucleus and identified a bipartite NLS in the CTD (Figure 1B) as the probable mediator of nuclear entry [37]. Previously thought as an artifact in the skin epithelium, nuclear neurofibromin is detected with a variety of techniques, i.e., immunocytochemistry (e.g., white arrows in Figure 3), subcellular fractionations, or proteomics [28,29,[37][38][39][51][52][53] in all cells of an ectodermal origin.…”
Section: Neurofibromins As Maps and Their Role In Mitosismentioning
confidence: 72%
“…The importance of NLS inclusion was totally unexplored, till we documented a few years ago that neurofibromin controls the pivotal function of chromosome congression on the mitotic spindle [38] (Figure 2) and then proved that depletion of NLS neurofibromins deregulates spindle assembly and positioning, leading to aneuploidy and increased micronuclei formation [39]. More importantly, these studies established the function of neurofibromins as MAPs.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations